The Influence of Economic Growth, Income Distribution Inequality, Unemployment Rate, Education, Health, Per Capita GDP, and Consumption on the Poverty Rate of Districts/Cities in West Sumatra from 2015-2024 - Viki Gusriadi; Ansofino; Yosi Eka Putri (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine: (1) the effect of economic growth on poverty in the regencies/cities of West Sumatra Province, (2) the effect of income distribution inequality on poverty in the regencies/cities of West Sumatra Province, (3) the effect of the unemployment rate on poverty in the regencies/cities of West Sumatra Province, (4) the effect of education on poverty in the regencies/cities of West Sumatra Province, (5) the effect of health on poverty in the regencies/cities of West Sumatra Province, (6) the effect of GRDP per capita on poverty in the regencies/cities of West Sumatra Province, (7) the effect of consumption on poverty in the regencies/cities of West Sumatra Province, and (8) the simultaneous effect of economic growth, income distribution inequality, unemployment, education, health, GRDP per capita, and consumption on poverty in the regencies/cities of West Sumatra Province. This research is a quantitative study conducted in West Sumatra Province from 2015–2024. The data used in this study are secondary data covering the years 2015–2024, with a total of 190 samples. The data collection techniques used were documentation and literature study, while the data were analyzed using panel data regression with the Eviews program. The results of the study show that: (1) an increase in all variables used in this study has an impact on poverty levels in the regencies/cities of West Sumatra Province. The greatest impact was found in the Mentawai Islands Regency at 25.941073 units, while the lowest was in Sawahlunto City at 24.410371 units. (2) An increase in economic growth affects poverty, with the highest impact in the Mentawai Islands Regency at 0.52864 units and the lowest in Sawahlunto City at -1.002062 units. (3) An increase in income distribution inequality impacts poverty, with the highest in the Mentawai Islands Regency at 0.707191 units and the lowest in Sawahlunto City at -0.823511 units. (4) An increase in unemployment affects poverty, with the highest impact in the Mentawai Islands Regency at 0.577847 units and the lowest in Sawahlunto City at -0.952855 units. (5) An increase in education influences poverty, with the highest in the Mentawai Islands Regency at 0.644134 units and the lowest in Sawahlunto City at -0.886568 units. (6) A decline in health affects poverty, with the highest impact in the Mentawai Islands Regency at -4.895513 units and the lowest in Sawahlunto City at -6.426215 units. (7) An increase in GRDP per capita influences poverty, with the highest impact in the Mentawai Islands Regency at -0.355639 units and the lowest in Sawahlunto City at -1.175063 units. (8) An increase in consumption affects poverty, with the highest impact in the Mentawai Islands Regency at 0.853609 units and the lowest in Sawahlunto City at -0.677093 units.